Jargon Iklan untuk Produk Lokal sebagai Industri Kreatif - Manurung, Rosida Tiurma (Zenit, 2014)
In the era of globalization, traditional or local foods are regarded as ”second hand products” by our society. The existence of regional foods is not appreciated. Even in culinary business, they are not considered significant at all. In this case, the advertisement (ad) jargons promoting regional foods are not creative, boring, and outdated; consequently, their existence is ignored. Progressive ad jargons play an important role as a creative industry to support local products. In the omnipresent of foreign products, jargons as on of the tools can be used to improve the popularity and image of localproducts. This research will discuss creative, unique, and marketable jargons; for instance, chocolates products in Garut have the following brands: Cokelat Antigalau (Anti-stress Chocolate), Cokelat Enteng Jodoh (Easy-to-get-soulmate Chocolate), Cokelat Cegah Alay (Foolish-avoidance Chocolate),Cokelat High Quality Jomblo (Unmarried High Quality Chocolate), Cokelat Antikorupsi (Anticorruption Chocolate), and so on, and all of which have positive images. It is high time that Indonesian regional foods made use of ad jargons for local cuisines. Regional foods represented by ad jargons as creative industry are supposed to show their existence in the market. Local consumers must also have the confidence that our regional foods also have high quality, competetiveness, and poistive images compared to foreign food products. Therefore, both local producers and ad designers must work hand in hand to enhance the product positive images while creating consumers’ interests to buy.Keywords: ad jargons, language strength, creative industry, local products, positive images